Natural course of muscular involvement assessed by a new computed tomography method in Duchenne muscular dystrophy. Issue 2 (26th March 2013) - Kuru, Satoshi; Sakai, Motoko; Tanaka, Nobuhiko; Konagaya, Masaaki; Nakayam, Takahiro; Kawai, Mitsuru
Abstract Aim Establishing the natural course of muscular impairment in Duchenne muscular dystrophy (DMD) is essential for defining the effect of treatments in clinical trials. We retrospectively investigated the change of thigh muscle volume in DMD using new indices, muscle volume index (MVI) and %MVI. Methods MVI is the estimated muscle volume contained within a given computed tomography (CT) slice and calculated using the CT histogram‐based procedure after correcting for a partial volume effect. %MVI is calculated by dividing the MVI by the entire volume of the region of interest. We applied this method to 49 retrospectively selected CT images from 21 patients with DMD, aged 6–13 years, at a relatively early stage. Results Both MVI and %MVI were found to have a significant inverse correlation with the clinical disability stage. In most patients, the changes over time in MVI and %MVI could be regressed to the exponential function Y = Ae−rX. The rate constant of the approximation curve was 0.299 ± 0.072 for MVI, and 0.351 ± 0.088 for %MVI, respectively. Conclusion MVI and %MVI have proven useful for follow‐up assessments of skeletal muscle volume in patients with DMD. Our retrospective longitudinal study should provide a basis for evaluating therapeutic interventions in future clinical trials.